RELIGIOUS POLICY OF THE RUSSIAN EMPIRE IN GALICIA ON THE EVE OF THE FIRST WORLD WAR - Baran, Ihor (Sworld-Us Conference proceedings, 2023)
The article examines the anti-Ukrainian activities of representatives of the Russian Orthodox Church in the territory of Eastern Galicia on the eve of the First World War. Cooperation between the church and the imperial authorities is well-founded and pr